2021
DOI: 10.1101/2021.05.06.442979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust IgM responses following vaccination are associated with prevention ofMycobacterium tuberculosisinfection in macaques

Abstract: Development of an effective tuberculosis (TB) vaccine has suffered from an incomplete understanding of the correlates of protection against Mycobacterium tuberculosis (Mtb). However, recent work has shown that compared to standard intradermal Bacille Calmette-Guerin (BCG) vaccination, intravenous (IV) BCG vaccination provides nearly complete protection against TB in rhesus macaques. While studies have focused on cellular immunity in this setting, the antibody response elicited by IV BCG vaccination remains inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Mycobacteria-specific IgM titers in plasma and BAL negatively correlated with Mtb burden in lungs (Irvine et al, 2021). LAM-specific antibodies from intravenously vaccinated macaques induced significantly (though moderately) higher antibody-dependent neutrophile phagocytosis (Irvine et al, 2021). Although endobronchial or intravenous vaccination may not be suitable routes for humans, these studies show that mycobacteria-specific antibodies can be protective and targeted by vaccine strategies.…”
Section: A Role For Antibodies In Tb Vaccinesmentioning
confidence: 91%
See 1 more Smart Citation
“…Mycobacteria-specific IgM titers in plasma and BAL negatively correlated with Mtb burden in lungs (Irvine et al, 2021). LAM-specific antibodies from intravenously vaccinated macaques induced significantly (though moderately) higher antibody-dependent neutrophile phagocytosis (Irvine et al, 2021). Although endobronchial or intravenous vaccination may not be suitable routes for humans, these studies show that mycobacteria-specific antibodies can be protective and targeted by vaccine strategies.…”
Section: A Role For Antibodies In Tb Vaccinesmentioning
confidence: 91%
“…Another study induced robust BCG-specific IgM responses in plasma and BAL by vaccinating macaques intravenously with BCG. Mycobacteria-specific IgM titers in plasma and BAL negatively correlated with Mtb burden in lungs (Irvine et al, 2021). LAM-specific antibodies from intravenously vaccinated macaques induced significantly (though moderately) higher antibody-dependent neutrophile phagocytosis (Irvine et al, 2021).…”
Section: A Role For Antibodies In Tb Vaccinesmentioning
confidence: 99%
“…They also had similar concentrations of IgG, IgM and IgA antibodies to different Mtb antigens as IGRA-positive contacts (6). Other studies, in humans (7) as well as primates (8), have also found in anti-Mtb antibodies, and suggested that they may protect against Mtb infection as well TB disease (9) in an IFN-γ-independent way.…”
Section: Introductionmentioning
confidence: 93%
“…The compartmentalization of immune responses between peripheral and local mucosa is well reviewed here ( 383 ). Recent studies have shown that aerosol and mucosal delivery of TB vaccine candidates help drive some IL-17-dependent cellular immunity ( 384 ) and increase vaccine-induced protective IgM antibody responses ( 385 ). Aerosol delivery of an adenovirus TB vaccine candidate has been described as safe and induces enhanced polyfunctional airway responses, including CD8+ T cells, outperforming intramuscular delivery of the same vaccine in mouse models of Mtb challenge ( 349 , 386 ) and a phase 1 human clinical trial ( 387 ).…”
Section: Review Of Clinical Stage Vaccine Candidates and Strategiesmentioning
confidence: 99%